Pressure controlled ventilation with volume guarantee improves outcomes in neonatal thoracoscopic esophageal atresia surgery - Kaimin, Lv; Bijun, Luo; Cheng, Luo; Xiaoxia, Wang (Frontiers in Pediatrics, 2025)
IntroductionNeonatal thoracoscopic repair of esophageal atresia requires one-lung ventilation (OLV), which poses challenges due to immature lung development and low compliance, increasing risks of hypoxemia and barotrauma. While volume-controlled ventilation (VCV) ensures stable tidal volume, it may cause excessive airway pressures, whereas pressure-controlled ventilation (PCV) lacks volume guarantee. This study compared PCV with volume guarantee (PCV-VG) and conventional VCV to improve respiratory outcomes during OLV.MethodsA retrospective analysis was conducted on neonates (aged 1–7 days) undergoing thoracoscopic esophageal atresia repair with OLV. Patients were categorized into PCV-VG and VCV groups. Respiratory parameters (PaO2, PaCO2, airway pressures, dynamic compliance) were measured before, during, and after OLV. Propensity score matching (PSM) was used to balance baseline characteristics.ResultsAfter PSM, 74 neonates (37 per group) were included. During OLV, the PCV-VG group exhibited significantly lower PaCO2, peak/mean airway pressures, and higher dynamic compliance compared to the VCV group (all P < 0.05). Postoperatively, PCV-VG was associated with shorter mechanical ventilation duration, ICU stay, and hospital stay (P < 0.05). Postoperative complication rates did not differ between groups (P > 0.05).ConclusionPCV-VG offers superior ventilation parameters and faster recovery in neonatal thoracoscopic esophageal atresia repair, though it does not affect postoperative complication rates.